Epidermal growth factor and bombesin act synergistically to support intestinal adaptation in rats with massive small bowel resection - YEGEN, BERRAK (SPRINGER, 2005)
Intestinal adaptation is the most important event in short bowel syndrome following a massive small bowel resection. Effects of various growth factors and their synergism have been well documented in intestinal adaptation. This study aimed to compare the effect of two different trophic agents, epidermal growth factor (EGF) and bombesin (BBS), on intestinal adaptation following massive intestinal resection. Sprague-Dawley male rats were assigned to one of four groups after a 75% small bowel resection. Either EGF (90 mu g/kg), BBS (10 mu g/kg), EGF+BBS, or bovine serum albumin (BSA) were injected subcutaneously three times a day. The animals were killed 10 days after the operation. Weight loss and morphologic parameters such as mucosal thickness, villus height, crypt depth, villus-to-crypt ratio, and muscularis propria height were measured. In the EGF+BBS group, mucosal thickness was found to be significantly increased compared with the other study groups (p < 0.05). Similarly, villus height was significantly increased only in the EGF+BBS group (p < 0.05). In the BBS group, both villus height and mucosal thickness showed a slight increase, but the values were not statistically significant compared with the vehicle-treated group. There were no significant differences in any of the remaining parameters between the groups. The results of this study indicate that the gut hormones EGF and BBS act synergistically in facilitating the adaptive response of the remnant ileum to massive intestinal resection.
Keywords: short bowel syndrome; epidermal growth factor; bombesin; FACTOR-ALPHA; BACTERIAL TRANSLOCATION; GASTROINTESTINAL-TRACT; MUCOSAL GROWTH; PROLIFERATION; PEPTIDES; THERAPY; HORMONE; INSULIN; INJURY